1995
DOI: 10.1046/j.1468-2982.1995.1501013.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Headache in Childhood and Adolescence: A Study in 437 Patients

Abstract: We investigated whether the criteria for idiopathic headache published by the International Headache Society (IHS) are useful in childhood and adolescence and compared the diagnoses according to this classification with those of Vahlquist. We used a semi-structured questionnaire to examine a total of 437 children and adolescents referred consecutively to a headache outpatient clinic. Twenty-eight of 437 patients were excluded because of symptomatic or unclassifiable headache. Of 409 patients with idiopathic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
134
5
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 30 publications
13
134
5
1
Order By: Relevance
“…The high rate of positive family history for migraine was consistent with Chu and Shinnar's study [10]. Nausea is less present than other neurovegetative signs in comparison with the school children and adolescents [18], probably because of children's incapability of describing this symptom.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high rate of positive family history for migraine was consistent with Chu and Shinnar's study [10]. Nausea is less present than other neurovegetative signs in comparison with the school children and adolescents [18], probably because of children's incapability of describing this symptom.…”
Section: Discussionsupporting
confidence: 86%
“…These data are hard to compare with other studies in this age because there are no studies that describe in a clear fashion the features of ETH in children at this age [19]. In two clinical-based studies [18,20] in school paediatric age the duration of headaches was reported more than in our data and there was more prevalence of associated symptoms and pulsatility. However, the duration of pain was the main limiting factor to classify the ETH according to the IHS criteria.…”
Section: Discussioncontrasting
confidence: 85%
“…Wober Bingol's [18] Population Study encountered prevalence of 3-17.6 % of migraine in adolescents. Describing pediatric headache, as a common health problem, Hershey found migraine in 10.6% of children between the age of 5 and 15 and in up to 28% of adolescents between the ages of 15 and 19 [19].…”
Section: Discussionmentioning
confidence: 99%
“…In 2.7% children aged 7 years and 10.6% children aged 14 years he defined migraine using Vahlquist's criteria [10]. Wöber-Bingöl et al's population study of migraine in children and adolescents [11] encountered migraine prevalence of 1.1%-5% in children and 3%-17.6% in adolescents. Zencir et al [12] found overall migraine prevalence was 8.8%; it was 6.7% in boys and 11.0% in girls (OR: 1.7; 95% CI: 1.3-2.3).…”
Section: Discussionmentioning
confidence: 99%
“…Analysing 409 children, Wöber-Bingöl et al [16] found the duration of migraine attacks was less than 2 h in 19.0% of migraine patients.…”
Section: Discussionmentioning
confidence: 99%